Yes, CARLA CAN: Extending the CARLA Simulator for In-Vehicle Network Cybersecurity Experimentation - Luz, Luigi F. Marques da; Ventura, Vinicius L.; Campelo, Divanilson R. (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2026: Anais Estendidos do XLIV Simpósio Brasileiro de Redes de Computadores e Sistemas DistribuídosDO - 10.5753/sbrc_estendido.2026.23250, 2026)
Modern vehicles rely on in-vehicle networks (IVNs), but protocols such as CAN lack built-in security, exposing critical systems to cyber threats. Existing platforms often require real vehicles or hardware, limiting accessibility. This work presents a software-based platform for automotive cybersecurity research and experimentation. It integrates a virtual CAN bus with dynamic driving scenarios using the CARLA simulator. A modular design enables ECUs (Electronic Control Units), attackers, and intrusion detection systems to operate as independent nodes. The platform enables monitoring and manipulation of CAN traffic without hardware, providing a reproducible environment for research, teaching, dataset generation, and evaluation of IVN security.